Neutropenia and Lymphocytopenia Among Arab Females with Iron Deficiency Anemia (IDA) and their Response to Iron therapy : IDA and cytopenia - Yassin, Mohamed; Almasri, Hussam; Al-Tikrity , Mustafa; Nashwan, Abdulqadir; Soliman, Ashraf (Acta Biomedica Atenei Parmensis, 2022)
. Introduction: The link between iron deficiency anemia (IDA) and neutropenia/ lymphocytopenia is not well established in the literature. This study aims at assessing the prevalence and clinical characteristics of neutropenia and lymphocytopenia in IDA patients considering the impact of iron replacement on the total and differential WBCs’ count. Subjects and Methods: The records of all female patients with IDA who attended our hematology clinic (Jan 2018 to Jan 2020) were retrospectively reviewed. Patients with systemic or chronic diseases were excluded. Age, BMI, CBC, and iron parameters were collected before and after IV iron therapy. Results: Out of 1,567 adult females with IDA, 80 patients had leukopenia (5.1%), 64 had neutropenia (4.0%), and 20 had lymphocytopenia (1.2%). After iron therapy, their mean leukocytes, neutrophils, and lymphocytes increased significantly to 4.38 ± 1.82 ×103/L, 2.3 ±1.56 ×109/L and 1.76 ± 0.48 ×103/L, respectively. About 67% of women with IDA and neutropenia had increased ANC in response to iron therapy. However, no significant correlation was found between leukocytes, ANC, or lymphocytes with TIBC or serum iron concentration. Conclusions: Neutropenia and/or lymphocytopenia may occur in patients with IDA and are reversible with iron therapy. Iron therapy led to the correction of anemia in 100% and increased ANC in 67%. Therefore, neutropenic women with IDA should be treated, initially only with iron, and observed for their Hb and ANC responses before starting any other treatment.